Outbreak of diarrhoea in piglets caused by novel rotavirus genotype G4P[49] in north‐western district of Bangladesh, February 2014. Issue 1 (11th September 2019) - Sarkar, Shamim; Esona, Mathew Dioh; Gautam, Rashi; Castro, Christina J.; Ng, Terry Fei Fan; Haque, Warda; Khan, Salah Uddin; Hossain, Mohammad Enayet; Rahman, Mohammed Ziaur; Gurley, Emily S.; Kennedy, Erin D.; Bowen, Michael D.; et al.
Abstract: Group A rotavirus (RVA) associated diarrhoea in piglets represents one of the major causes of morbidity and mortality in pig farms worldwide. A diarrhoea outbreak occurred among nomadic piglets in north‐western district of Bangladesh in February 2014. Outbreak investigation was performed to identify the cause, epidemiologic and clinical features of the outbreak. Rectal swabs and clinical information were collected from diarrhoeic piglets ( n  = 36). Rectal swabs were tested for RVA RNA by real‐time reverse transcription polymerase chain reaction (rRT‐PCR) using NSP3‐specific primers. The G (VP7) and P (VP4) genes were typed by conventional RT‐PCR and sanger sequencing and full genome sequences were determined using next‐generation sequencing. We found the attack rate was 61% (50/82) among piglets in the nomadic pig herd, and the case fatality rate was 20% (10/50) among piglets with diarrhoea. All study piglets cases had watery diarrhoea, lack of appetite or reluctance to move. A novel RVA strain with a new P[49] genotype combined with G4 was identified among all piglets with diarrhoea. The genome constellation of the novel RVA strains was determined to be G4‐P[49]‐I1‐R1‐C1‐M1‐A8‐N1‐T7‐E1‐H1. Genetic analysis shows that the novel G4P[49] strain is similar to Indian and Chinese porcine or porcine‐like G4 human strains and is genetically distant from Bangladeshi human G4 strains. Identification of this novel RVA strain warrants further exploration for disease severity and zoonotic potential.